Analysis of engagement factor in trajectory tracking-based experiment - Ismail, Elliana; Sidek, Shahrul Na'im; Khan, Md. Raisuddin; Jalaludin, Nor Anija (2012)
The main objective of this work is to study the degree of engagement levels of human subjects in completing a series of tasks based on their physiological signals. The tasks are in the form of tracking a set of trajectories on the computer screen by using a mouse. . The subjects are chosen randomly based on both sexes, aged from 20 to 40 years old. After completing the required tasks in a series of experiments, the subjects are given a set of questions to answer In particular, for the experiment, the subjects are asked to track a set of prescribed paths within the allocated times in order to adhere to different speed constraints. Various shapes of trajectories with various colours are given to the subjects in order to study the degree of engagements while performing the tasks. In estimating the degree of engagement level, the physiological signals; namely the electrooculogram (EOG) are recorded by using the Gtec data acquisition system. By using these signals, information on the endogenous type of eye blinking is extracted. After completing the experiments, a set of questionnaires are given to the subjects to measure the degree of engagement level. The questionnaire works as an important tool to validate the engagement model deduced from the experiment done earlier by the subjects. Preliminary analysis on the questionnaire shows a good match